Slipped through the narrow door: Effects of climate change on the distribution and conservation of a vulnerable tiger gecko, Goniurosaurus luii, from China and Vietnam - Hai Ngoc Ngo; Tao Thien Nguyen; Hoang Huy Nguyen; Truong Quang Nguyen; Huy Quoc Nguyen; Hien Thu Thi Ngo; Huong Thu Thi Nguyen; Linh Thuy Thi Ha; Larry Lee Grismer; Dennis Rödder; Thomas Ziegler (Nature Conservation)
Under human impacts, the global effects of climate change are exacerbating the biodiversity crisis with an anticipated high level of extinction risk for many species. As a range-restricted tropical specialist existing in small and fragmented populations, the likelihood of survival under future climate change is significantly reduced for Goniurosaurus species due to the loss of genetic diversity caused by population declines and habitat destruction. Predictions indicated that three Vietnamese tiger gecko species (G. catbaensis, G. lichtenfelderi and G. huuliensis) will be potentially impacted by climate change. It is projected that similar scenarios of climate change may also affect a highly specialized species, G. luii, restricted to karst habitats in mainland southern China and northern Vietnam. In this study, we develop a species distribution model using MaxEnt, trained on climatic data to project the current potential distribution of G. luii. To assess future impacts of climate change, we used climate change scenarios of three Shared Socioeconomic Pathways (i.e. ssp245, ssp370, ssp585) over 20-year periods (i.e. 2050s, 2070s and 2090s). Our models projected the potential distribution of G. luii mainly covering the sites of occurrence and their surroundings in the border between China and Vietnam, among which 3,175 km2 are karst habitats containing highly climatic suitability. All scenarios of climate change projected a significantly smaller area of high suitability compared to the current prediction and even no highly suitable habitat was documented in pathways of ssp370 by 2070s and 2090s, and ssp585 by 2090s. Given the potential impacts of climate change in the future, we highlight the border area between China (e.g. southern Guangxi Province) and Vietnam (e.g. northern Cao Bang and Lang Son provinces) as priority region for habitat protection.